Planning and Optimization of Motor Transport Enterprise Manpower - D. L. Karzhytski (Наука и техника)
Efficiency of enterprise activity is determined by comparison of the obtained data and the expended resources (financial, tangible, labour). At the same time successful enterprise activity mainly depends on efficiency of manpower utilization. While developing a theory of human capital workers of enterprises are considered as their capital. These statements propose certain requirements to optimization of manpower. The main purpose of optimization is not simply quantitative change in manpower or its structure but determination of efficiency rate which is obtained by an employer as a result of rational utilization of enterprise personnel and measure of losses due to non-rational utilization.